Tanggung Jawab Hukum Platform Pinjaman Online terhadap Penyalahgunaan dan Penyebaran Data Pribadi Konsumen secara Ilegal - Naswa Fiolla Anggraini; Sidi Ahyar Wiraguna (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study aims to analyze the legal responsibilities that can be imposed on online lending platform organizers for the misuse and illegal distribution of consumer personal data. With the rapid development of the online lending industry, the issue of protecting consumer personal data has become a very important issue. Misuse of personal data can have serious impacts on consumers, including identity theft and financial loss. Therefore, this study examines the forms of legal responsibilities that can be applied, such as administrative, criminal, and civil responsibilities, as well as the obstacles faced in their implementation. This study uses a normative approach with an analysis of applicable regulations, namely the Personal Data Protection Law (UU PDP), the Electronic Information and Transactions Law (UU ITE), and other related regulations. Data were obtained through a literature review covering relevant laws and regulations, journals, articles, and case studies. The results of the study indicate that online lending platform organizers can be subject to three forms of legal responsibilities. Administrative responsibilities include sanctions imposed by supervisory authorities such as the Financial Services Authority (OJK) and the Personal Data Protection Agency (BPDP). Criminal responsibilities can be in the form of imprisonment and fines for those who violate provisions related to personal data protection. Civil liability gives consumers the right to file a lawsuit for losses caused by a breach of their personal data. This study also identified various obstacles in implementing legal liability, such as lack of awareness of organizers, difficulties in supervision, and legal loopholes in user agreements.